PENGELOLAAN OBJEK WISATA KAMPOENG RABBITS KOTA PEKANBARU - Nurul Hidayah; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Management of tourist objects is something that must be considered properly so as not to disappoint visitors who come. This research was conducted at the Kampoeng Rabbit's tourist attraction, Pekanbaru City. The Kampoeng Rabbit's tourism object in Pekanbaru City is an education-based tourist attraction about the first rabbit in Pekanbaru City. The management of Kampoeng Rabbit's tourism object in Pekanbaru City consists of planning, organizing, actuating and controlling. This study aims to determine the management of the Kampoeng Rabbit's tourist attraction, the existing obstacles and the management's efforts to overcome the obstacles that exist in the Kampoeng Rabbit's tourist attraction. Data collection techniques were carried out by means of observation, interviews and documentation with data collection techniques through key informant purposive sampling. This study describes the general description of the Kampoeng Rabbit's tourist attraction in Pekanbaru City and how to manage the Kampoeng Rabbit's tourist attraction, the obstacles and how the efforts made by the manager in overcoming the obstacles that exist in the Kampoeng Rabbit's tourist attraction. Keywords: Management, Tourism Objects, Educational Tourism.